STRENGTH ANALYSIS AND TEST OF FABRIC REINFORCED AIRSHIP ENVELOPE (MT) - LIU Yang; ZHAO HaiTao; ZHANG Jun; GAO ChengJun; CHEN JiAn (Jixie qiangdu)
In order to study the strength performance of the airship envelope and the influence of overpressure bearing on its residual strength, the sample forms and experiments plans for the uniaxial and biaxial tensile of the envelope material were designed, and the tearing situation of the airship was analyzed with the help of a high-speed camera. Based on the experimental data, fitted the uniaxial tensile strength curve when the airship bears air pressure, and the longitudinal and latitudinal strength envelope line of the material when it was biaxially stretched. The experimental results demonstrate that there is a negative correlation between the residual strength of the envelope and the airship bearing air pressure when uniaxially stretched, the bearing strength of the envelope is comprehensively affected by the longitudinal and latitudinal strengths when biaxially stretched. This experiment also analyzes the failure situation of the airship envelope, which can provide an experimental guidance for its strength prediction.